Meningkatkan Hasil Belajar IPS Kelas 5 SD Menggunakan Model PBL, Mind Mapping dan Talking Stick - Erly Noorliana, Khairil Anwar (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2023)
The purpose of this study was to determine teacher and student activities and improve student learning outcomes. This type of Classroom Action Research (PTK) was conducted in four sessions. The research environment was 17 students in semester 2 of SDN Kuin Selatan 1 Banjarmasin in 2022/2023. The types of data used are qualitative and quantitative, with qualitative data from teacher and student activity observation sheets and quantitative data from learning outcomes determined by group tests and learning assessments. The results of this study indicate that teacher activity in each session continues to increase from a score of 19 "good" criteria to a score of 27 "very good" criteria in cycle II meeting 2. Student activity also increased in cycle I meeting 1 obtained 47% "Moderately Active" criteria and increased in cycle II meeting 2 to 88% "Very Active" criteria. Likewise, student learning outcomes at the first meeting in cycle I meeting 1 obtained 23% classical completeness and increased in cycle II meeting 2 to 100%. Based on the research results, it was concluded that the combination of PBL, Mind Mapping and Talking Stick learning models. This study aims to improve teacher activity, student activity, and improve can improve student learning outcomes.